The Politics of Envy: Envy in Aristotle's Political Thought - Rupčié, Tina (My University, 2000)
Political theorists have identified envy to be of political concern. While it is generally agreed that certain forms of envy are socially disruptive, there is relatively little agreement as to the nature of this threat, and how to address it. This difference seems to stem from different understandings of the nature of the emotion itself. This thesis examines the place of envy within the context of Aristotle's political philosophy. Aristotle, it is argued, has an accurate understanding of the nature of envy and he offers a political arrangement that seems to successfully undermine the most socially dangerous forms of envy, without compromising the potential for social progress. Aristotle recognizes that envy arises when one is insecure or anxious with respect to their own self-worth. He presents a political arrangement that is designed to engender a more secure basis for individual self-worth, which is also feasible among those who lack this security.
Keywords: Political Science; Political Science